FAKTOR-FAKTOR YANG MEMPENGARUHI KEBERHASILAN PENGOBATAN TUBERKULOSIS PARU - Nurmasadi ' Kurniawan; Siti Rahmalia HD; Ganis Indriati ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2015)
Abstract   Pulmonary tuberculosis (PT) is one of between two diseases (tuberculosis extrapulmonary) which includes 80% of the overall disease events PT. Control efforts TB nationally by implement strategies DOTS. DOTS strategy recommended WHO globally because result in the case finding and successful of high treatment.The purpose of this study was to determine the factors influence successful treatment of pulmonary tuberculosis in Puskesmas Harapan Raya 2013. The research is descriptive with cross sectional approach. The number of sample were 43 respondents taken by total sampling with data collected tool was patientsregisters TB data retrieval using with retrospective. The data collection was analyzed by univariate and bivariate using with Fisher's Exact test. The univariat results showed that the agesofmajority respondents was age of productive (83,7%), male (69,8%), compliance of treatment (69,8%), smear-negative for tuberculosis (76,7%) and used drug of cathegory I (95,3%). The bivariate analyzed showed that significant relationship between compliance level and smear-negative for tuberculosisand age with type of treatment (ρ value 0,000 < 0,05 and ρ value 0,023 < 0,05). The results showed there was not significant relationship between age and smear-negative for tuberculosis, sex and smear-negative for tuberculosis, sex and type of treatment, and compliance level with type of treatment (ρ value 0,656 > 0,05, ρ value 0,237 > 0,05, ρ value 0,086 > 0,05, dan ρ value 1,000 > 0,05). Based on results of this study, it is suggest to people who have awareness, willingness, and ability to improve the knowledge and compliance in completing treatment of pulmonary tuberculosis.   Keyword: age, level of compliance, pulmonary tuberculosis, sex,smear for tuberculosismicroscopic examination after treatment, type of treatment